Impact of digital media on public administration - A. M. Evloev; I. V. Goncharova (Управление)
This article examines the influence of digital mass media on public administration processes in the context of the modern era of digitalisation. The relevance of the topic is due to the rapid development of digital technologies and their integration into everyday human life, which certainly affects the interaction of society and government. The consequences of digitalisation for the media environment are analysed. Special attention is paid to the digital mass media as an object of research, their structure and functions, the interdisciplinary nature of scientific approaches and a variety of interpretations are emphasised. The difficulties of scientific understanding of this phenomenon are revealed. The importance of the digital media for public administration is considered, including improving communication between government agencies and citizens, increasing transparency and accountability of the government as well as opportunities for involving the citizens in decision-making processes. The role of modern digital services, in particular “Gosulugi”, in the development of new format communications is emphasised. In conclusion, the article focuses on the need to adapt government structures to the new conditions in order to maximise the potential of the digital mass media in the interests of sustainable development and democratisation of governance. With the increasing complexity of the digital media landscape, there is a need to create a digital media strategy to achieve specific goals of the public administration.